Pembangunan dan Penilaian Prestasi Medan Uji Kajian Rangkaian IPv6 Di Universiti Utara Malaysia - Asmahizan, Sahizah (2007)
There are numerous amounts of limitations in IPv4, namely, the shortage of IP addresses. Many of the IPv4's limitations and problems solution lies in IPv6. Thus, this research is conducted with the focus on setting up an IPv6 testbed that will serve as initial step for large scale IPv6 network deployment. The implementation involves two location within UUM network namely Pusat Komputer and Fakulti Teknologi Maklumat. This development of IPv6 testbed is the first project of it kind in UUM. IPv6 prototype application has been developed. The prototyping functions as a tool to evaluate the performance of the testbed. Various tests have been conducted to ensure that the application has been properly developed and are functioning well. Performance evaluation processes are conducted by running an IPv6 application that has been developed in the test bed environment. The transmitted packets in the testing processes were captured and analyzed using Ethereal packet analysis tool. The captured results are shown to verify that the application is running on IPv6 network. The connection testing also included the ping and traceroute tools which their result had been analyzed to evaluate the testbed performance. This research has delivered an IPv6 testbed that is useful and beneficial to the community of UUM and allowing them to utilize the IPv6 application in the future. Through this study, we hope to identify some problems in implementing the IPv6 testbed before any real implementation to be done.